An Investigation in Attention Bias Modification Training: Attention Bias Assessment, Acquisition and Change with the Dot-Probe Task - Mergelsberg, Enrique Laurent Paul (Curtin University, 2019)
Attention bias change can reduce anxiety vulnerability. The mechanisms that underlie attention bias assessment and training with the dot-probe task are unclear. This research project investigated the main stimulus-probe associative learning mechanism within the dot-probe task. It compared the attentional engagement and disengagement processes that underlie attention bias change using the dot-probe task and a gamified attention training task. The current work aids the understanding of successful attention bias assessment, acquisition and change.